Tightening the employment of immigrants: a comparative analysis between Malaysia and Singapore / Nur Amirah Mohd Hanifah, Nur Ulfa Ghazali and Muhammad Zulfaqar al Basysyar Saharuddin - Mohd Hanifah, Nur Amirah; Ghazali, Nur Ulfa; Saharuddin, Muhammad Zulfaqar al Basysyar (2013)
The purpose of this thesis is to examine the effectiveness of laws on foreign workers in Malaysia. Hitherto, the influx of foreign workers in Malaysia is too common, yet the situation has been overwhelming when illegal immigrants who enter Malaysia without a valid permit. Besides, this thesis discusses the inability of the law to control the influx of illegal immigrants. Additional issues involving migrant workers are also discussed such as issues permits, employment passes, and the impact of the influx of foreign workers. We are also able to identify the rights granted to foreign workers and the extent to which that right may be applied by them. The law such as the Employment Act 1955 and Immigration Act 1959/63 list the rights and procedures of foreign workers, but there is failure in the enforcement from the public authorities. In addition, comparative study with neighbouring country, Singapore is made as the country is capable of controlling the numbers of foreign workers. It is hoped that from this research, the country can amend the current laws to provide balance in employment sector as to prioritise the locals as well as dealing successfully to curb this situation.